Self-inflicted bilateral ocular and eyelid injuries in an unsuspected individual. Issue 2 (May 2019) - Samia-Aly, Emma; Ha, Jerome; Sagili, Suresh
Background and aims: This report aims to illustrate a case of self-inflicted ocular and orbital injury, resulting in severe tissue loss and ophthalmoplegia in a patient with no known history of mental illness. Methods and results: A 71-year-old male initially presented to the emergency department with significant tissue loss from his left upper and lower lids, orbital tissue loss and complete ophthalmoplegia, after reportedly tripping and falling onto his desk. He subsequently attended the emergency department on two further occasions with similar injuries, affecting the same and contralateral eye, whilst maintaining a traumatic cause for his injuries. He was eventually admitted to a psychiatric ward for mental health assessment. This report covers his progress as well as illustrating his injuries with images. Conclusion: Self-harm is an important differential diagnosis in cases where the mechanism of injury does not correspond to the extent of injury or tissue loss. It can, however, be difficult to differentiate from accidental injury and even with repeated assessments, a formal psychiatric diagnosis may not be possible.